2001
DOI: 10.1046/j.1365-2133.2001.04515.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in molecular killing mechanisms: implications in skin disease

Abstract: Cytolytic T lymphocytes exert two main specific molecular killing mechanisms against target cells, namely (i) they can synthesize and release soluble cytolytic factors, and (ii) they can express effector molecules that act as ligands of receptors expressed by target cells on the cell surface; by these two pathways cytolytic T lymphocytes kill several targets, e.g. cells infected with intracellular pathogens, cells transformed by malignancy and cells producing autoantibodies. This review investigates the contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Its extracellular C‐terminal domain can be proteolytically cleaved to form soluble TRAIL. Both the membrane and soluble forms of TRAIL induce apoptosis in a variety of primary cells and tumour cell lines via activation of cell‐surface death receptors 5,6,9,18–20 . TRAIL expression has been reported in human epidermis, notably in the basal layers, infundibulum and the outer root sheath of hair follicles 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Its extracellular C‐terminal domain can be proteolytically cleaved to form soluble TRAIL. Both the membrane and soluble forms of TRAIL induce apoptosis in a variety of primary cells and tumour cell lines via activation of cell‐surface death receptors 5,6,9,18–20 . TRAIL expression has been reported in human epidermis, notably in the basal layers, infundibulum and the outer root sheath of hair follicles 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the question of the prognostic value of regulatory T-cells in melanoma and focused more specifically on the frequency of Tregs, related to the stage of the illness. Mourmouras et al investigated the proportion of Tregs within cutaneous melanocytic lesions including stage I melanomas and found a lower percentage of Tregs in vertical compared to radial growth phase melanomas (23), whereas De Panfilis et al described the contrary and also a higher prevalence of Tregs in stage III-IV melanomas compared with stage I tumors (24). In a study performed in vertical growth phase melanomas, Miracco et al found that high intra-and peritumoral proportion of Tregs predicted local recurrence (25).…”
Section: Discussionmentioning
confidence: 99%
“…The cell death of epidermal cells carrying a hapten, caused by these CTL killing mechanisms, in turn, may favor the release, upon lethal hit, of a wide array of inflammatory cytokines and chemokines [25], responsible both for the cutaneous inflammation and for the clinical picture of allergic contact dermatitis/contact hypersensitivity [28]. In summary, allergic contact dermatitis and contact hypersensitivity are mediated by CD8+ hapten-specific CTL, which may use either the Fas-L/Fas or the perforin pathway to elicit skin inflammation [29].…”
Section: Molecular Killing Mechanismsmentioning
confidence: 99%